Group Evaluations of Individual Faculty Hospitalists - Alliston, Deborah; Kelt, Matthew J.; Nehme, Grace; Wittler, Robert (Kansas Journal of Medicine, 2019)
IntroductionFaculty evaluations are important tools for improving faculty-to-resident instruction, but residents in our pediatric and internal medicine/pediatric residency programs would seldom evaluate individual pediatric faculty hospitalists. Our objectives were to: (1) increase the percentage of completed evaluations of individual pediatric hospitalists to greater than 85%, (2) improve the quality of pediatric hospitalist feedback as measured by resident and faculty satisfaction surveys, and (3) to reduce the resident concern of lack of anonymity of evaluations.MethodsMembers of the resident inpatient team (pediatric and internal medicine/pediatric residents) completed group-based evaluations of individual pediatric hospitalists. A survey to evaluate this change in process was distributed to the pediatric hospitalists (n = 6) and another survey was distributed to residents, both based on a 5-point Likert-type scale. Surveys were completed before and four months after implementation of the changes. Pre- and post-survey data of resident and hospitalist responses were compared using the Mann-Whitney test and probability proportion test.ResultsThe percent of completed evaluations increased from 0% to 86% in one month and to 100% in two months. Thereafter, the percent of completed evaluations remained at 100% through the end of the data collection period at seven months. Hospitalists reported (n = 6, 100% participation) their satisfaction regarding the feedback they received from residents significantly increased for all survey questions. Resident satisfaction (n = 24, 89% participation in postintervention surveys) increased significantly with regards to the evaluation process.ConclusionsFor hospitalists, group-based resident evaluations of individual hospitalists led to an increased percentage of completed evaluations, improved the quality and quantity of feedback to hospitalists, and increased satisfaction with evaluations. For residents, these changes led to increased satisfaction with the evaluation process.